Disaster risk construction in the progressive consolidation of informal settlements: Iquique and Puerto Montt (Chile) case studies. (September 2015) - Castro, Carmen Paz; Ibarra, Ignacio; Lukas, Michael; Ortiz, Jorge; Sarmiento, Juan Pablo
Abstract: The relationship between informality and vulnerability, common in Latin American communities, is analyzed using data from two medium-sized cities in the Chilean urban system as case studies: Iquique, located in the northern desert zone of the country, and Puerto Montt, located in the rainy south. Informal settlements, or ' campamento' (literally meaning campsites in Chile), within these cities were studied and analyzed. The results revealed that while these originally illegal campamentos have gradually been absorbed by urban sprawl and have reached internal consolidation, they continue to maintain their conditions of precariousness and social vulnerability. The campamento settlements are frequently located in areas exposed to natural hazards. They have also been subject to institutional backwardness, or a lack of oversight, with little to no attention being paid to risk reduction. In Iquique, the campamentos located in the northern zone of the city are highly exposed to seismic threats and landslides. They are also close to the port and the tax free zone (ZOFRI). In the case of Puerto Montt, the most vulnerable areas of the campamentos are the coastline areas to the west and east of the city, which are subject to landslides and flooding. The campamento settlements constitute real vulnerability hotspots for their residents, as they are high risk zones within the cities, characterized by high levels of precariousness. In general, they have not been considered in the urban improvement measures, even though they have been part of each city's main urban area for several decades now.